Analysis of Factors that Influence Accounting Students Choose Career As A Public Accountant - Fu'at Hasim; Novi Darmayanti; A. Manaf Dientri (Master of Accounting Universitas Trunojoyo Madura, 2020)
The selection of a career for students of accounting was the initial stage of the establishment of a career. After completion of the period of study College, career options for graduates in accounting not addressed only on the accounting profession but there were also other options for a career. There were several factors that affect students' career selection accounting for a career in public accounting. A sample of 115 students accounting for UNISDA and UNISLA. Methods of analysis used was logistic regression with SPSS version 22. The type of data being used was the primary data obtained from the questionnaire respondents. From the results of testing hypotheses obtained that the factors of financial rewards and social values significantly influential partially against the interest of the students in the choosing a career as a public accountant.